2020
DOI: 10.1016/j.mri.2019.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Tagged cine magnetic resonance imaging to quantify regional mechanical changes after acute myocardial infarction

Abstract: Purpose:The conventional volumetric approaches of measuring cardiac function are loaddependent, and are not able to discriminate functional changes in the infarct, transition and remote myocardium. We examined phase-dependent regional mechanical changes in the infarct, transition and remote regions after acute myocardial infarction (MI) in a preclinical mouse model using cardiovascular magnetic resonance imaging (CMR). Methods:We induced acute MI in six mice with left anterior descending coronary artery ligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Götte et al compared regional function between the infarcted and remote region and found significant differences by CMR tissue tagging but not by wall thickening analysis (11). An animal study, quantifying regional mechanical changes 2 weeks after index procedure by tagged cine, also presented similar results, in which circumferential strain was −1.5 ± 0.5%, −4.5 ± 0.8%, and −5.5 ± 1.4% in infarct zone, transition zone, and remote zone, respectively (direct comparison was not performed) (28). Our study performed in a larger human population and by a more convenient method (CMR feature-tracking) showed that strains in adjacent region were better than infarcted region and worse than remote region.…”
Section: Discussionmentioning
confidence: 67%
“…Götte et al compared regional function between the infarcted and remote region and found significant differences by CMR tissue tagging but not by wall thickening analysis (11). An animal study, quantifying regional mechanical changes 2 weeks after index procedure by tagged cine, also presented similar results, in which circumferential strain was −1.5 ± 0.5%, −4.5 ± 0.8%, and −5.5 ± 1.4% in infarct zone, transition zone, and remote zone, respectively (direct comparison was not performed) (28). Our study performed in a larger human population and by a more convenient method (CMR feature-tracking) showed that strains in adjacent region were better than infarcted region and worse than remote region.…”
Section: Discussionmentioning
confidence: 67%
“…Then, delayed enhanced images were obtained 2–10 min after intravenous (IV) gadolinium injection (Omniscan 0.1 mmol/kg) using previously validated inversion recovery pulse sequence. The TI Cardiac function and strain imaging was performed by using Segment version 3.1 R8123 ( http://segment.heiberg.se accessed on 15 June 2020), as described previously by our group [ 14 - 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Strain analysis was conducted on amyloidosis patients using principles from finite strain theory, as described previously [ 14 ]. Cardiomyocyte contraction was evaluated by using one-dimensional Lagrangian strains ( ε ) along the circumferential, radial and longitudinal directions, which are defined by the following formula [ 19 ]: where L is the length of the myocardial segment and L 0 is the original length at end diastole.…”
Section: Methodsmentioning
confidence: 99%
“…Each motion pattern is related to a different myocardial layer, which allows the derivation of the location and severity of the impairment [ 15 ]. Strain imaging has shown its incremental value to improve diagnosis and quantification of wall motion disturbances in acute and chronic ischemic cardiomyopathy in preclinical animal models [ 16 ] and human studies [ 17 – 19 ]. Recent publications demonstrated the incremental prognostic value of strain imaging in risk stratification after myocardial infarction [ 20 23 ].…”
Section: Functional Analysis To Evaluate Wall Motion Disturbances Andmentioning
confidence: 99%